Structural and sequence analysis of the RPO30 gene of sheeppox and goatpox viruses from India - Gundallahalli Bayyappa Manjunatha Reddy; Krishnappa Sumana; Revanaiah Yogisharadhya; Hosakote Venkatappa Mohan; Vijaykumar Kolar Lavanya; Basavarajappa Harlipura Chethankumar; Nayakwadi Shivasharanappa; Mani Saminathan; Sajjanar Basavaraj; Kuldeep Dhama; Shivachandra Bhadravati Sathish (Veterinary Quarterly)
Sheeppox and goatpox are transboundary viral diseases of sheep and goats that cause significant economic losses to small and marginal farmers worldwide, including India. Members of the genus Capripoxvirus (CaPV), namely Sheeppox virus (SPPV), Goatpox virus (GTPV), and Lumpy skin disease virus (LSDV), are antigenically similar, and species differentiation can only be accomplished using molecular approaches. The present study aimed to understand the molecular epidemiology and host specificity of SPPV and GTPV circulating in India through sequencing and structural analysis of the RNA polymerase subunit-30 kDa (RPO30) gene. A total of 29 field isolates from sheep (n = 19) and goats (n = 10) belonging to different geographical regions of India during the period: Year 2015 to 2023, were analyzed based on the sequence and structure of the full-length RPO30 gene/protein. Phylogenetically, all the CaPV isolates were separated into three major clusters: SPPV, GTPV, and LSDV. Multiple sequence alignment revealed a highly conserved RPO30 gene, with a stretch of 21 nucleotide deletion in all SPPV isolates. Additionally, the RPO30 gene of the Indian SPPV and GTPV isolates possessed several species-specific conserved signature residues/motifs that could act as genotyping markers. Secondary structure analysis of the RPO30 protein showed four α-helices, two loops, and three turns, similar to that of the E4L protein of vaccinia virus (VACV). All the isolates in the present study exhibited host preferences across different states of India. Therefore, in order to protect vulnerable small ruminants from poxviral infections, it is recommended to take into consideration a homologous vaccination strategy.